Silver-Spotted Skipper; Epargyreus clarus (Cramer) (Insecta: Lepidoptera: Hesperidae: Pyrginae) - Donald W. Hall (EDIS)
EENY-439, a 5-page illustrated fact sheet by Donald W. Hall, is part of the Featured Creatures Collection of fact sheets. It describes one of the largest, most widespread and most recognizable skippers, characterized by a large white spot on the underside of each hind wing — its distribution, description, life cycle and biology, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, July 2008.